PENGARUH KEPERCAYAAN DIRI, MOTIVASI DAN LITERASI TERHADAP PRESTASI AKADEMIK MAHASISWA UMS MASA PANDEMI COVID-19 - Nabiel Irsyad; Niken Damayanti; Nur Muhammad Arrizky; Karunia Za'idah; Rahma 'Afifah Nur Faridah (Universitas Tribhuwana Tunggadewi, 2021)
The purpose was to investigate the influence of self-confidence, motivation and literacy on the academic achievement of the students of Muhammadiyah University of Surakarta in the pandemic Covid-19. This research was used a quantitative with an online questionnaire. The population in this research was an active students from 12 faculties with 146 respondents of samples, the calculation using the technique of calculation of random. Data analysis technique used is the test validity, test reliability, test of normality and regression test (anova) using the application of statistics SPSS 23. Validity indicates the degree of accuracy between the real data in the field and data objects of the researcher, while reability performed by repeated measurements. Normality test is used to determine the data that has been collected normal distribution. Regression test showed the influence between variables, i.e., free variables and bound in research. The results showed that the influence of selfconfidence, motivation and literacy on the academic achievement of the students of Muhammadiyah University of Surakarta in the pandemic Covid-19 has a positive influence. Seen on the influence of motivation has a value of influence by 72%, the influence of self-confidence has the value of the effect of 18%, while the influence of literacy has a value of influence pealing small amounting to 14%. Based on the results of research that has been done is bestowed if literacy have a slight impact on academic achievement of students. Therefore, the need for encouragement to the students to improve the culture of literacy in the form of advice and adequate infrastructure in the scope of the university even faculty with the aim to improve the academic achievement of students.